KETAHANAN PANGAN DAN COPING STRATEGY RUMAH TANGGA URBAN FARMING PERTANIAN DAN PERIKANAN KOTA SURABAYA - Fika Mayrlina Anggrayni; Dini Ririn Andrias; Merryana Adriani (Universitas Airlangga, 2015)
Rapid urbanization in urban areas causes dissimilarity of food access in each household. It is become one of urban food security problem. Urban farming is a strategy to improve food access in urban areas. The purpose of this study was to analyze the difference in food security and coping strategy of agriculture and fisheries urban farming households. This observational study used a cross-sectional design. A sample of 62 households were divided into 2 groups: agriculture and fisheries urban farming households. Food security was assessed by United States Household Food Security Survey Module (US-HFSSM) questionnaire while coping strategy was assessed by Reduced Coping Strategy Index (RCSI) questionnaire. The difference of household food security and coping strategy in both groups was analyzed by Chi square test. A total of 64,7% household in agriculture group were in food secured, while 75% households in fishery group were in food insecure with severe hunger degrees. There was no difference of household food security between agriculture and fisheries urban farming group (p = 0,255), although two groups had different in food security status. Most of agriculture urban farming household has RCSI score <14 (65,6%), while the majority of fishery urban farming household has RCSI score ≥ 14 (66,7%). There was a difference of coping strategy between agriculture and fishery urban farming household (p = 0,021). Agriculture urban farming households were secured and rarely do coping strategy compared to fishery urban farming households. Government programs to improve food security should be more focused on groups of fishery urban farming households.Keywords: coping strategy, food security, household, urban farming